2022
DOI: 10.1007/s10495-022-01779-0
|View full text |Cite
|
Sign up to set email alerts
|

DNMT2/TRDMT1 gene knockout compromises doxorubicin-induced unfolded protein response and sensitizes cancer cells to ER stress-induced apoptosis

Abstract: The acidic, hypoxic and nutrient-deprived tumor microenvironment may induce endoplasmic reticulum (ER) stress and the unfolded protein response (UPR) may exert an important cytoprotective role by promoting folding of newly synthesized proteins and cancer cell survival. The lack of DNMT2/TRDMT1 methyltransferase-mediated C38 tRNA methylation compromises translational fidelity that may result in the accumulation of misfolded and aggregated proteins leading to proteotoxic stress-related cell death. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 86 publications
1
8
0
Order By: Relevance
“…Finally, siRNA knock-down of DNMT2 increased protein aggregation levels, in agreement with previous studies (Fig. S 7B ) [ 47 ]. Altogether, these results show that the immunopeptidome of AZA-treated cells is significantly impacted by the DNMT2 inhibition mediated by AZA.…”
Section: Resultssupporting
confidence: 92%
“…Finally, siRNA knock-down of DNMT2 increased protein aggregation levels, in agreement with previous studies (Fig. S 7B ) [ 47 ]. Altogether, these results show that the immunopeptidome of AZA-treated cells is significantly impacted by the DNMT2 inhibition mediated by AZA.…”
Section: Resultssupporting
confidence: 92%
“…TRDMT1 KO also affected the levels of 5-methylcytosine RNA methyltransferase NSUN family in chemotherapy-stimulated senescent glioblastoma cells [ 14 ]. Furthermore, TRDMT1 KO modulated microRNA pools during doxorubicin-induced ER stress in glioblastoma cells [ 15 ]. Thus, TRDMT1 may regulate gene expression by different mechanisms in glioblastoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, we have shown that apart from TRDMT1-mediated regulation of gene expression by RNA modification [ 20 ], microRNA [ 15 ] and lcnRNA [ 23 ], TRDMT1 may be also a modulator of DNA methylation-based epigenetic control of gene expression. However, more studies are needed to reveal a molecular mechanism of TRDMT1-associated modulation of DNA methylome and its consequences in cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above study illustrates that the expression level of ER stress related proteins is associated with the occurrence and development of cervical cancer. ER stress activation might have a high value in the treatment and prognosis of cervical cancer and has good clinical prospects [71,72].…”
Section: Cervical Cancermentioning
confidence: 99%